Social judgeability effect on the «ultimate attribution error» - Kamenov, Željka (2008)
The aim of the research was to test the social judgeability theory in intergroup causal attribution. According to Pettigrew's « ; ultimate attribution error» ; (UAE), when making judgments about the causes of someone's actions people make favorable attributions for the behaviors of their ingroup members, and unfavourable ones for the members of the out-groups. However, the empirical evidence of the UAE is not so strong and conclusive and to help explain this we focused on the (in)appropriateness of biased social judgment in certain circumstances. The experiment combining within and between groups design was conducted with 189 undergraduate students of Croatian nationality. Within-group variables were type of behavior (positive/negative) and actor’ s group membership (in-group/out-group). Between-group variables were type of the out-group (neutral/negatively valued), type of individual information about the actor (irrelevant/pseudo-relevant) and timing of presenting the individual information (with the categorial information or delayed). The dependent variable was the judgment about the internal causality of the described behavior. The results were partialy in line with the social judgeability theory, particulary when explaining the causes for negative behaviors. Although participants did not make UAE when categorial information was presented, the additional presentation of irrelevant and pseudo-relevant individual information about the actor led to different effects, depending on the actor’ s group membership. The significant difference in attribution patterns was found between people with high and low levels of national identity, as well as between low and high self-monitors.
Projekt MZOS
ENG